2020
DOI: 10.1002/cbic.202000656
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Lipid Bilayer Ion Permeability by Antibacterial Polymethyloxazoline‐Polyethyleneimine Copolymers

Abstract: Amphiphilic antimicrobial polymers display activity against the outer bacterial cell membrane, triggering various physiological effects. We investigated the regulation of ion transport across the lipid bilayer to understand differences in biological activity for a series of amphiphilic polymethyloxazoline – polyethyleneimine copolymers. The results confirmed that the tested structures were able to increase the permeability of the lipid bilayer (LB) membrane or its rupture. Black lipid membrane (BLM) experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Zeta-potential of polymeric aggregates was measured using the dynamic light scattering (DLS) technique. This property influences the membrane lytic mechanism of polymers, [55,71] particularly at the stage of initial electrostatic interactions between a polycation and negatively charged phospholipid bilayer. Obtained results indicate that aggregates of C8-D-PEG and C12-D-PEG are characterized by a substantially lower surface charge than their nonPEGylated counterparts.…”
Section: Polymer Synthesis and Characterizationmentioning
confidence: 99%
“…Zeta-potential of polymeric aggregates was measured using the dynamic light scattering (DLS) technique. This property influences the membrane lytic mechanism of polymers, [55,71] particularly at the stage of initial electrostatic interactions between a polycation and negatively charged phospholipid bilayer. Obtained results indicate that aggregates of C8-D-PEG and C12-D-PEG are characterized by a substantially lower surface charge than their nonPEGylated counterparts.…”
Section: Polymer Synthesis and Characterizationmentioning
confidence: 99%
“…One of the best methods for the evaluation of membrane quality changes and their bioelectric properties is the black lipid membrane technique. In recent decades, this well-established method has been extensively used to study a plethora of antibacterial copolymers, ionophoric agents and ion channels, including those found in intracellular membranes [ 16 , 27 , 28 ]. To our knowledge, a study on the interactions between PM and biological membranes has not been reported yet, leaving some open questions: Does PM permeabilize biological membranes?…”
Section: Discussionmentioning
confidence: 99%